Classifying body physique and elite zones in modern elite athletes with Hattori chart: a scoping review - Martinez-Mireles, X.; Ramírez-López, E.; López-García, R.; Lagunes-Carrasco, J. O. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
The Hattori chart method (Hattori et al, Am. J. Hum. Biol.,1997,9,573-578) utilizes the fat-free mass index (FFMI) and fat mass index (FMI) to represent body physique, combined with body fat percentage (%BF) and body mass index (BMI). This method has primarily been applied to elite athletes in gymnastics, fencing and combat sports. Despite the increasing availability of body composition studies on international athletes, the identification of elite zones in modern elite athletes remains unresolved. This study aims to determine body physique using the Hattori chart and to identify elite zones in modern elite athletes. Following PRISMA-ScR guidelines, a search across ten databases was conducted for articles published between 1995 and 2024 using the terms "anthropometric" AND "elite athlete." Forty-seven studies focused on anthropometry were included. The %BF and BMI were calculated using weighted means, the data from Frisancho (Frisancho, Univ. Mich. Press.,2008,2nd) for individuals aged 20.0 to 29.9 years were used for FFMI and FMI, and elite zones were established at ± 2 standard deviations (SD). Male elite athletes displayed a "lean intermediate" body physique, characterized by intermediate FFMI and low FMI, with elite zones at a BMI of 24.1 ± 4.4 kg/m2 and %BF of 14.0 ± 11.0. Female athletes showed an "intermediate" physique characterized by intermediate FFMI and FMI, with elite zones at a BMI of 22.5 ± 2.2 kg/m2 and %BF of 22.4 ± 8.8. The SD showed four categories of body physique that predominated in the athletes: intermediate, solid intermediate, lean intermediate, and solid intermediate. Some athletes were outside the elite zone due to body physiques with high FFMI and FMI. Identifying elite zones can help sports scientists optimize training regimens for body composition improvement. This is the first study to systematically identify elite zones across multiple sports, offering a framework for future athlete physique assessments using the Hattori chart. Further research is recommended to differentiate by sport categories, positions, specialties, and macrocycle periods.